G171(P) Innovative core community paediatrics training. (12th March 2018) - Merchant, N; Thakur, D; Sheth, P
Abstract : Introduction: Paediatric curriculum mandates that all paediatric trainees achieve Community Paediatrics (CP) competencies as a part of their core (Level 2) training in the United Kingdom. However there are concerns that shift-based hospital training does not allow dedicated community training time. Aim: To evaluate and streamline core-community training rotations. Methods: Feedback from the community and hospital teams, showed need to improve continous exposure in CP for better learning experience, achievement of competencies and improve patient care and safety. Using Quality Improvement Methodology key changes and ideas were implemented (table 1). Dedicated CP training was the key change in practice needed alongside supporting hospital service. An innovative block of 4 months (instead of the traditional 6 months) training was designed and piloted. This was tailored to allow achievement of CP competencies whilst mainting continuity and hospital requirements. Trainees spent weekdays in CP and maintained some hospital commitments out-of-hours during weekdays only. An initial pilot was set up with 2 trainees as described above. Monthly consultant trainee forum allowed feedback from both groups trainees and consultants. This was followed by an anonymous questionnaire evaluating the training. Results: Including annual leave, the 4 month block over 18 weeks provided 608 community hours vs 503 hours in the traditional 6 month rotation over 26 weeks. 3 consultants and 7 trainees have completed the survey over the last 12 months. All felt that there was improved continuous exposure with better learning, more clinic attendance, increased assessment completion, better attendance of training opportunities. The initial trainees in the pilot felt they more likely to come in their own time to complete assessments. This was reviewed and structured timetables along with mid-supervision meetings were implemented. There were mixed views about audit completion. Conclusion: A 4 month community rotation met training needs efficiently without impacting on hospital based training and service provision. It had trainee and consultant satisfaction. A 4 month community block would also allow more trainees to be hospital-based during the busy winter season.